Institutional solutions of administrative decision-making "De lege ferenda" with European standards - Selimić, Mirzo (Crisis Management Days, 2024)
In order to conduct a comprehensive examination, this paper requires the establishment of the following basic hypotheses: (1) factual change of the law on the administrative procedure is an inevitable phenomenon, even in a system with a constitution as it is in Bosnia and Herzegovina, which for a long time indubitably requires thorough changes; (2) factual legal change is more common in constitutional systems that in practice are characterized by exceptional strength, which is particularly the case in countries with a complex state structure, divided society and a fragmented political scene, such as in Bosnia and Herzegovina; (3) Bosnia and Herzegovina, despite its constitutional rigidity, has undergone numerous factual constitutional changes that have had different manifestations and that, therefore, require new provisions to the law on administrative space in order to bring it into line with the European administrative space and provisions based on European standards of the so-called "good governance". Based on this set of hypotheses, research questions arise: (1) identification of different forms of factual legal change in the theory and practice of administrative law; (2) precise determination of the manner in which the law on the administrative procedure would undergo factual changes; (3) harmonization of factual legal changes in comparative administrative law, specifically the law of the European Union and its member states; (4) how the legal-theoretical conceptualization of this issue was carried out in the theory of administrative systems of other countries. In order to reach relevant insights, it is necessary to ponder in detail the theoretical considerations of the phenomenon of factual changes in the law on administrative procedure. Given this issue has largely been neglected in domestic literature for numerous reasons, which are mostly denoted in the numerous published works, round tables, and conferences, this issue will require an insight into the literature outside the administrative area of Bosnia and Herzegovina, especially from countries where the phenomenon was already present and where the theory and practice of administrative law had to face it more directly. Following the classification of these manifestations, it will be necessary to approach their individual detailed analysis, both in order to better understand the phenomenon at hand in general and in order to more precisely apply general understandings and knowledge to a specific example of Bosnian administrative procedural law.